The importance of lipoprotein(a) in the development of cardiovascular diseases (CARDIOLOGY OF UZBEKISTAN, 2025)
Aim. To study the impact of lipoprotein (a) levels on major cardiovascular events. Materials and methods. We examined the impact of lipoprotein(a) levels on major cardiovascular events based on a review of articles on this topic. Results. Based on a review of articles on this topic, it can be said that Lp(a) is a highly atherothrombogenic lipoprotein associated with atherosclerotic cardiovascular diseases and their complications, in particular, ischemic heart disease and aortic valve stenosis. Conclusion. Lipoprotein (a) levels may serve as a criterion for determining residual risk during hypolipidemic therapy.